Metformin from mother to unborn child – are there unwarranted effects? - Nguyen, Linh (2018)
For more than 40 years, metformin has been used before and during pregnancy. However, it is important to note that metformin can cross the placenta and circulate in the developing foetus. Recent studies reported that the concentration of metformin in foetal cord blood ranges from half to nearly the same concentration as in the maternal plasma. Since metformin has anti-cell growth and pro-apoptotic effects, there are persistent concerns over the use of metformin in early pregnancy. Current human studies are limited by sample size, lack of controls or, short follow-up durations. In this review, we examine the settings in which metformin can be passed on from mother to child during pregnancy and address the current controversies relating to the cellular and molecular mechanisms of metformin. Our efforts highlight the need for more data on the effects of metformin on general offspring health as well as further scrutiny into foetal development upon exposure to metformin.